(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article discusses the process of teaching students the basic technical movements of the volleyball game in physical education classes. It analyzes the educational significance of the volleyball game, methods for gradually teaching technical elements, and the possibilities of using modern pedagogical technologies.